Mycology of otomycosis and the role of antifungal drops versus antifungal cream in the treatment of otomycosis: an observational study - Lekha, V. Sneha; Priyadarshini, Neelima; Pakanati, Siva Subba Rao; Kumar, K. Dilip (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Aim of the study was to determine most common mode of presentation, spectrum of fungi involved in otomycosis and to compare the treatment efficacy of 1% clotrimazole drops with 1% clotrimazole cream in management of otomycosis. Methods: A prospective observational study was conducted over a study period of 18 months, in which a total of 60 patients who are clinically diagnosed with otomycosis were included. All the specimens collected from patients were subjected to standard microbiological procedures for identification of fungi involved in otomycosis. Then patients were randomly allotted into 2 groups for treatment with 1% clotrimazole drops or with cream. Improvement in symptoms of pain, pruritis, blocked sensation, and discharge on one-and two-weeks follow-up was recorded. External auditory canal was evaluated for improvement in otomycotic debris. All patients were asked the opinion about preferred modality of treatment. Results: In our study, Aspergillus niger 27(45%) was the predominant species isolated. When compared to the symptoms on day 01 at day 07, significant difference was noted for the improvement of the symptoms and also for the otomycotic debris in both the groups. The group with cream had significantly more blocked sensation. On second week follow up, significant improvement was noted for all the symptoms and otomycotic debris. Forty five out of sixty patients preferred using cream. Conclusions: In our study, Aspergillus species was found to be the commonest fungi involved in otomycosis. 1% topical clotrimazole drops and cream were equally effective in management of otomycosis.